So the doves - James, Heidi, 1973- (Dover Publications, Inc., 2019)
Marcus Murray was only 17 when his best friend Melanie vanished from his hometown in oceanside Kent. Afterward, she seemed like a figment of his imagination <U+2014> she became a story, a myth, a series of actions and consequences incorporated into his own history. Working as a journalist years later, Marcus is flush with success at having uncovered a corrupt alliance between a U.K. bank, the arms trade, and the government. So he's a bit disconcerted when sent from London back to Kent to report on the finding of a corpse during a railway excavation. Worse yet, his moral and professional triumph is called into question by charges of fabrication. While Marcus chafes at his exile and fears for his reputation, the hometown atmosphere evokes thoughts of the long-lost Melanie and her mysterious disappearance. Recounted in chapters that alternate between events from 1989 to the present, So the Doves poses thought-provoking questions about identity, offering a poignant meditation on memory and loss.